2012
DOI: 10.1111/clr.12077
|View full text |Cite
|
Sign up to set email alerts
|

The effect of load on heat production, thermal effects and expenditure of time during implant site preparation – an experimental ex vivo comparison between piezosurgery and conventional drilling

Abstract: PS yields significantly higher temperatures and thermal tissue alterations on load levels higher than 500 g and is significantly slower for ISP compared to SB and TB. For ISP with PS, a maximum load of 400 g should be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 37 publications
(45 reference statements)
2
84
0
7
Order By: Relevance
“…However, different literature data have been reported on this issue (23-25). Stelzle et al (26) observed a highest thermal impact in the cortical bone with both piezoelectric and rotating techniques supporting the hypothesis that cortical bone is more susceptible of temperature rise than cancellous bone. In the first set of osteotomies the highest mean values for ΔTmax occurred with IM1s (Tab.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…However, different literature data have been reported on this issue (23-25). Stelzle et al (26) observed a highest thermal impact in the cortical bone with both piezoelectric and rotating techniques supporting the hypothesis that cortical bone is more susceptible of temperature rise than cancellous bone. In the first set of osteotomies the highest mean values for ΔTmax occurred with IM1s (Tab.…”
Section: Resultsmentioning
confidence: 81%
“…Speed, pressure, irrigation and bur shape have been identified as some of the most important factors influencing temperatures rising (3). The impact of pressure and irrigation has been also investigated with respect to implant site preparation with piezoelectric instruments (26,27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, to our knowledge only 2 methods have been used to record the heat generated in real time. Thermocouples, which enable direct measurement, 3,5,7,13,[15][16][17][18]23,24,26,35 were first reported in implant dentistry by Horch and Keiditsch. 36 Infrared thermography provides an indirect estimate, 4,18,22,27 and measurements were first described by D'Hodet et al 37 Although thermocouple technology is well established, studies on its use are still not uniform (Table 1), and there are variations in the distance to the final cut (between 0.5 and 2 mm), configuration of the elements (from mono to tripod), and depths and numbers in the vertical dimension (monochannel and multichannel).…”
Section: Study Modelsmentioning
confidence: 99%